An Integrated Framework for Assessing Vulnerability to Climate Change and Developing Adaptation Strategies for Coffee Growing Families in Mesoamerica - Baca, María; Läderach, Peter R.D.; Haggar, Jeremy P.; Schroth, Götz; Ovalle Rivera, Oriana (International Center for Tropical Agriculture, 2016)
Experts predict that the climate change will affect all natural and human systems. Historical climate records show changes in average and extreme temperatures, as well as an increase in annual climate variability; this changes can affect all continents of our planet in different ways and the high levels of poverty in some regions can worsen the impacts of climate change. In addition, families who are dedicated to making agriculture and owning small land units directly dependent on its production to keep your family economy. The purpose of this research was to identify levels of vulnerability of coffee farming families in four countries of the Mesoamerican Region (Nicaragua, Guatemala, El Salvador and Mexico), because coffee is an important livelihood for thousands of families in this region. In order to know the response of crops to projected changes, the state of their resources and ultimately the strategies that they can implement to minimize the impact of climate change, this research was done using climate models to project the coffee climate suitability and the exposure in this regions; also qualitative tools were combined under the focus on livelihoods and resources of families to identify the vulnerability level.